2014
DOI: 10.1111/mec.12608
|View full text |Cite
|
Sign up to set email alerts
|

‘Becoming a species by becoming a pest’ or how two maize pests of the genus Ostrinia possibly evolved through parallel ecological speciation events

Abstract: New agricultural pest species attacking introduced crops may evolve from pre-existing local herbivores by ecological speciation, thereby becoming a species by becoming a pest. We compare the evolutionary pathways by which two maize pests (the Asian and the European corn borers, ACB and ECB) in the genus Ostrinia (Lepidoptera, Crambidae) probably diverged from an ancestral species close to the current Adzuki bean borer (ABB). We typed larval Ostrinia populations collected on maize and dicotyledons across China … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(59 citation statements)
references
References 80 publications
(121 reference statements)
4
50
5
Order By: Relevance
“…Ostrinia nubilalis is an emerging model for speciation dynamics due to sympatric ecotypes or strains that vary in voltinism and sex‐pheromone communication (Coates et al, ; Dopman et al, ; Kozak et al, ; Lassance, ; Olsson et al, ). Ecological differences in host plant preference occur between closely related O. nubilalis strains in North America (O'Rourke et al, ) and among Ostrinia species in Europe (Bethenod et al, ; Bourguet, Bethenod, Trouve, & Viard, ; Bourguet et al, ; Frolov et al, ; Pélozuelo, Malosse, Genestier, Guenego, & Frérot, ; Pélozuelo et al, ; Thomas, Bethenod, Pelozuelo, Frérot, & Bourguet, ). Although pheromone system and host plant use co‐vary in Ostrinia (Alexandre et al, ), elucidating the relative contribution of various selective forces to differentiation in the presence of high rates of gene flow remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ostrinia nubilalis is an emerging model for speciation dynamics due to sympatric ecotypes or strains that vary in voltinism and sex‐pheromone communication (Coates et al, ; Dopman et al, ; Kozak et al, ; Lassance, ; Olsson et al, ). Ecological differences in host plant preference occur between closely related O. nubilalis strains in North America (O'Rourke et al, ) and among Ostrinia species in Europe (Bethenod et al, ; Bourguet, Bethenod, Trouve, & Viard, ; Bourguet et al, ; Frolov et al, ; Pélozuelo, Malosse, Genestier, Guenego, & Frérot, ; Pélozuelo et al, ; Thomas, Bethenod, Pelozuelo, Frérot, & Bourguet, ). Although pheromone system and host plant use co‐vary in Ostrinia (Alexandre et al, ), elucidating the relative contribution of various selective forces to differentiation in the presence of high rates of gene flow remains a challenge.…”
Section: Discussionmentioning
confidence: 99%
“…In France, Ostrinia populations using the alternative pheromone blends of E11‐ and Z11‐14:OAc were initially assumed to be E‐ and Z‐strain O. nubilalis . Strong associations were demonstrated among moths using the Z‐pheromone communication system for maize (C4) and the E‐system moths for C3 host plants (Bontemps et al, ; Bourguet et al, ) which were accompanied by significant levels of genetic differentiation (Bethenod et al, ; Malausa et al, ). However, subsequent studies concluded that Ostrinia using the E‐pheromone system in France were O. scapulalis , and a different species compared to sympatric Z‐strain O. nubilalis (Calcagno, Bonhomme, Thomas, Singer, & Bourguet, ; Frolov, Bourguet, & Ponsard, ; Malausa et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Moth populations on maize are reproductively isolated from populations that feed on mugwort (Calcagno et al, 2007;Bourguet et al, 2014). The two host races also appear to be genetically isolated.…”
Section: Human-mediated Migration Of Crops Triggers Host Shiftsmentioning
confidence: 99%
“…Native herbivore populations that shift onto agricultural crops can become genetically differentiated from populations that remain on the original host plant (Vialatte et al, 2005;Michel et al, 2010;Lavandero et al, 2011 Midamegbe et al, 2011;Barman et al, 2012;Bourguet et al, 2014). Because host shifts create new ecological opportunities for herbivores, population can diverge via ecological speciation in sympatry (Bush, 1969;Berlocher and Feder, 2002).…”
Section: Human-mediated Migration Of Crops Triggers Host Shiftsmentioning
confidence: 99%
See 1 more Smart Citation